Integrating Technologies in the New Normal: A Study of Blended Learning - Rahma Sakina; Eva Meidi Kulsum; Aip Syaepul Uyun (International Journal of Quantitative Research and Modeling, 2020)
The objective of this research is to describe how the teacher integrates technologies in blended learning and to analyze students’ perception and challenges in blended learning. The research was conducted in a private senior high school in Bandung and used a qualitative descriptive method. The data were collected through interview and questionnaire. The findings show that the teacher had already integrated technologies to run the process of teaching and learning in the new normal era as a replacement of a face to face learning due to Covid-19 pandemic. In the blended learning, the teacher integrated the variety of technologies in teaching-learning activities, namely zoom meeting and WhatsApp group chatting for the synchronous learning and she utilized google classroom, screencast o matic screen recorder, viva video editor, YouTube, and Quizizz the synchronous learning. The students perceived  blended learning positively and determined that it is it is one of the effective ways of teaching. The biggest challenge overcome by the teacher is more time needed to learn and adapt to this new situation where they must employ technology in our educational culture. For the students, the stability of internet connection also becomes major obstacle in blended learning. Apart from that, blended learning can be an option applied in the learning process in the current pandemic era.